2014
DOI: 10.1152/ajpgi.00253.2013
|View full text |Cite
|
Sign up to set email alerts
|

Dietary flaxseed intake exacerbates acute colonic mucosal injury and inflammation induced by dextran sodium sulfate

Abstract: Flaxseed (FS), a dietary oilseed, contains a variety of anti-inflammatory bioactives, including fermentable fiber, phenolic compounds (lignans), and the n-3 polyunsaturated fatty acid (PUFA) α-linolenic acid. The objective of this study was to determine the effects of FS and its n-3 PUFA-rich kernel or lignan- and soluble fiber-rich hull on colitis severity in a mouse model of acute colonic inflammation. C57BL/6 male mice were fed a basal diet (negative control) or a basal diet supplemented with 10% FS, 6% ker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
2
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 101 publications
(114 reference statements)
2
35
2
2
Order By: Relevance
“…In contrast to the findings in humans, mouse models of colitis induced by carrageenan and DSS have demonstrated that classical and alternative NF-B signaling pathways are activated (12,13,81,84) during colonic inflammation. One of the earliest events in IBD is thought to be impairment of enteric mucosal barrier function.…”
Section: Alternative Pathway Nf-b Signaling In Conditions Of the Gastcontrasting
confidence: 69%
See 1 more Smart Citation
“…In contrast to the findings in humans, mouse models of colitis induced by carrageenan and DSS have demonstrated that classical and alternative NF-B signaling pathways are activated (12,13,81,84) during colonic inflammation. One of the earliest events in IBD is thought to be impairment of enteric mucosal barrier function.…”
Section: Alternative Pathway Nf-b Signaling In Conditions Of the Gastcontrasting
confidence: 69%
“…In contrast, the use of dietary flaxseed to attempt to ameliorate experimental colitis was found to exacerbate DSS-induced colitis in mice, which was associated with an increase in expression of RelB in colonic tissue (84). Together these studies highlight the functional effect that foods may have on NF-B alternative pathway signaling in the gastrointestinal tract.…”
Section: Alternative Pathway Nf-b Signaling In Conditions Of the Gastmentioning
confidence: 97%
“…Edible plants have been shown to produce anti‐inflammatory effects in various experimental colitis murine models . However, only very limited research focused on the effects of edible mushrooms on intestinal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Diets exacerbate colitis by increasing the disease activity index, colonic injury, apoptosis, myeloperoxidase, and cytokines like IL‐6 and IL‐1β, and NF‐κB‐related genes, namely Nfkb1, Ccl5, Bcl2a1a, Egfr, Relb, Birc3, and Atf1. Serum cytokines such as IL‐6, IFN‐γ, IL‐1β, and hepatic cholesterol levels were also increased, indicating systemic toxicity (Zarepoor et al , ).…”
Section: Phytochemicals For Management Of Inflammatory Bowel Diseasementioning
confidence: 99%